The retinoblastoma gene product is a cell cycle-dependent, nuclear matrix-associated protein. - Mancini, M A (1994)
The retinoblastoma gene product (Rb) has been established as a tumor suppressor and cell cycle regulator, although its mechanism of action remains obscure. The observations that several Rb-binding viral oncoproteins all associate with the nuclear matrix suggest that these interactions may occur on this structure. To determine whether Rb itself is a component of the matrix, we extracted synchronized cultured cells to isolate matrix proteins while preserving nuclear architecture. Immunoblot and immunolabeling data show that a significant portion of hypophosphorylated Rb associates with the matrix only during early G1. Mutant Rb in tumor cells did not associate with the matrix, whereas Rb-reconstituted cells contained abundant matrix-bound Rb. Rb is distributed widely throughout the matrix, particularly concentrated at the nuclear periphery and in nucleolar remnants. Core filaments of the matrix contained no detectable Rb. Our screening of expression libraries for potential Rb-associated proteins has identified several that are part of the matrix. Specifically, the peripheral matrix proteins lamin A and C bound Rb in vitro. We therefore suggest that Rb interactions with the nuclear matrix may be important for its ability to regulate cell cycle progression.